PARENTS' PERCEPTION AND INVOLVEMENT TOWARD ENGLISH FOR YOUNG LEARNERS IN RUSTIC AREA - Islam, Raudhatul (At- Ta'lim : Jurnal Pendidikan, 2023)
The aimed of this research was to analysed the parents perception and their involvement toward the important of EYL in rustic area. To investigate the kind of phenomena specifically, qualitative approach is needed to applied in this research which employed a case study design. This study was conducted in Pakuniran village, Pakuniran district, Probolinggo East Java Province. This village is chosen because Pakuniran become one of the remote area in this distric but children enthusiasm in teaching and learning english is higher. The data was obtained through observation, interview and questionnaire. Fifteen parents from kindegarten and primary school volunteered to be the participants for responding to their choices in the questionnaire. Five parents of students (i.e. p1, p2, p3, p4, and p5) in each level were requested to perceive the perception and involvement in their children's English ability. The subjects were selected using Purposive Sampling techniques. The result of this research that parents' perception and their involvement toward EYL in rustic area, in this case is Pakuniran village Probolinggo Regency have positive response. Parents involvement becomes one of the biggest support systems to success in teaching and learning. Choosing the best school for their education child, additional English learning outside are the ways of parents’ support.